Effect of Calcination Temperature on Structural Properties and Photocatalytic Activity of TiO2/Vermiculite Composite for Methylene Blue Degradation - Nam Dao Duy; Trang Vu Minh; Hai Huynh Trung; Ha Thi Thu Vu (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
This study investigated the effect of calcination temperature on the structural properties and photocatalytic performance of TiO2/vermiculite (TiO2/ver) composites for methylene blue (MB) degradation. The TiO2/ver composites were synthesized via a one-step sol-gel method using titanium (IV) isopropoxide (TTIP) as the precursor, followed by calcination at 450, 600 and 800 oC. Structural characterization by X-ray diffraction (XRD) revealed that the anatase phase predominance in samples calcined at 450 and 600 oC, whereas partial transformation to rutile occurred at 800 oC. Scanning electron microscopy (SEM) showed that increasing calcination temperature promoted particle growth and agglomeration. Fourier-transform infrared (FT-IR) analysis revealed the coexistence of characteristic Ti-O-Ti and Si-O vibrations and indicated possible interfacial interactions between TiO2 and the vermiculite support through a shift the Si-O stretching band. Textural analysis demonstrated a progressive decrease in specific surface area with increasing calcination temperature, suggesting thermally induced pore collapse and crystallite growth. Photocatalytic experiments demonstrated that the sample calcined at 450 oC (V-450) exhibited the highest photocatalytic activity, achieving complete MB degradation within 90 min under the optimal conditions of a catalyst dosage of 1.0 g.L-1, an initial MB concentration of 10 mg.L-1 and pH of 7. Kinetic analysis showed that the degradation followed pseudo-first-order kinetics. The superior performance of the V-450 was attributed to the optimal balance between crystallinity, specific surface area and phase composition. These findings highlight the critical role of calcination temperature in tuning the structure-activity relationship of TiO2/ver composites for photocatalytic wastewater treatment applications. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).